Nilai-Nilai Pendidikan Islam dalam Al-Quran Surat Luqman Ayat 12-13 dan Implikasinya terhadap Pendidikan Masyarakat 5.0 di MTs Ar-Rahmah - Maulana Restu, Yanto; Ahmad Firdausa, Eidat; Zaenudin, Udin; Munasir (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
This research was conducted to examine the values of Islamic education in the Koran surah Luqman verses 12-13 and their implications for community education 5.0 at MTs Ar- Rahmah. The study is motivated by an era that is increasingly developing, such as the emergence of a new era, namely society 5.0 which is based on all forms of technology integrated into everyday life, and the internet is used for more than just information where Islamic education has not fully adhered to Islamic values. completely, thus making the crisis of faith a lack of that wise attitude and gratitude. This is a challenge for the world of Islamic education so that they are able to have abilities in the era of community education 5.0 and remain based on Islam. Al-Quran as a source of Islamic education provides overall solutions and contributions along with the development of knowledge from the verses of the Koran related to education. This study aims to answer the educational values in surah Luqman verses 12-13, how is community education 5.0 according to Luqman verses 12-13 and its implications at MTs Ar-Rahmah. In this study, researchers used a methodology with a qualitative approach. This type of research is descriptive qualitative. Field research or descriptive approach. Collecting research data using observation literature, interviews and documentation. The results of this study indicate that the values of Islamic education in surah Luqman verses 12-13 have implications for community education 5.0 at MTs Ar-Rahmah.